2011
DOI: 10.1007/s12291-011-0141-3
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin Polymorphism and Association with Complications in Ghanaian Type 2 Diabetic Patients

Abstract: There is scanty information on the role of genetic factors, especially those relating to haptoglobin (Hp) phenotypes in the expression of complications among diabetes mellitus patients in Ghana. In this study, we investigated whether there is any association between Hp phenotypes and diabetic complications and to determine if association of the Hp phenotypes with diabetic complications in Ghanaian diabetics differ from those in Caucasians. A total of 398 participants were randomly recruited into the study. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 44 publications
3
12
1
Order By: Relevance
“…There are many reports on HP phenotypes, diabetes, and its complications from many parts of the world. [37, 38, 39, 40, 41, 42, 43, 44] This was similar with Quaye et al , study that concluded that HP2-2 allele was a risk factor for type 2 diabetes in Ghana, whereas the HP1-1 allele appeared protective. [37] However, this finding contrasts with previous observation in American-Indian studies where HP allele was a risk factor.…”
Section: Discussionsupporting
confidence: 82%
“…There are many reports on HP phenotypes, diabetes, and its complications from many parts of the world. [37, 38, 39, 40, 41, 42, 43, 44] This was similar with Quaye et al , study that concluded that HP2-2 allele was a risk factor for type 2 diabetes in Ghana, whereas the HP1-1 allele appeared protective. [37] However, this finding contrasts with previous observation in American-Indian studies where HP allele was a risk factor.…”
Section: Discussionsupporting
confidence: 82%
“…Fasting blood glucose levels for the non -diabetic participants were within the reference range and were significantly lower compared to the levels for the T2DM participants. This confirms other reports [15,18].…”
Section: Discussionsupporting
confidence: 94%
“…Contrary to this, a population study by Stern et al [22] indicated that diabetes is associated with the Hp1-1 phenotypes. Results from Adinotey et al [15] presented investigation in Ghanaians and support the position that diabetes is associated with Hp phenotypes. Their finding confirmed what has been earlier on reported [16].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations